Faktor Yang Berhubungan Dengan Kejadian Kekurangam Energi Kronik (KEK) Pada Ibu Hamil Di Wilayah Kerja Puskesmas Martapura 1 - Hayati, Rahmi; dewi, Vonny Khresna; Hipni, Rubiati; Kirana, Rita (JURNAL KEBIDANAN BESTARI, 2024)
Chronic Energy Deficiency (CED) in pregnant women is a condition where the mother lacks protein and energy during pregnancy which can result in health problems for the mother and fetus. This study aims to determine the factors associated with the incidence of CED in pregnant women in the Martapura Community Health Center Work Area 1. This study uses type Quantitative research with design analytical correlation cross sectional. A sample of 90 pregnant women used purposive sampling. The independent variables are income, knowledge, age of pregnant women, parity and distance between pregnancies, while the dependent variable is KEK pregnant women. Data collection was carried out by looking at the latest MCH examination book and measuring the mother's LILA, after that distributing questionnaires. This type of research data is ordinal, analyzed through computerization. The results of the study showed that there was a relationship in all variables with the incidence of CED. There were 90 samples, 36 respondents (40.0%) who experienced CED and 54 respondents (60.0%) who did not experience CED. There is a relationship between income P value = 0.014, knowledge P value = 0.032, and parity P value = 0.034 with KEK. The conclusion is that there is a relationship between income, knowledge, and parity the incidence of CED in pregnant women in the Martapura Community Health Center Work Area 1Keywords: Factors, CED